New Certificateless Blind Ring Signature Scheme - Hua Sun (Institute of Advanced Engineering and Science, 2014)
A new certificateless blind ring signature scheme was proposed in this paper. The scheme could not only avoid the problem of certificate management of public key certificate cryptography, but also overcome the inherent key-escrow problem of identity-based public key cryptography. In the last, by using bilinear pairing technique, it was proved that this scheme satisfied the security of existential unforgeability, blindness and unconditional anonymity. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3382